Use of Foreign Language as Greeting in Restaurants, Especially Chung Gi Wa Restaurant Bandung - Jelita Rabbani; Faleri Dharma Putri (Momentum Matrix: International Journal of Communication, Tourism, and Social Economic Trends, 2024)
The use of foreign languages as greetings at Restaurants Chung Gi Wa in Bandung reflects a smart communications strategy in the hospitality industry . In the context of globalization and customers diversification , using Korean as a foreigner language in greetings offers significant impacts on the restaurant's image , staff-customer interactions , and overalls customers experience . This research employs a qualitative method to analyze how the use of foreign languages , particularly Korean , influences customers perceptions of the restaurants . The findings indicate that using Korean creates an authentic and consistent image with the restaurant's theme , enhancing the appeal for customers seeking a genuine Korean culinary experience . Moreover , staff-customer interactions are positive affected by using foreign languages as greetings , fostering closer and more personalized relationships .